High-density deformation nanotwin induced significant improvement in the plasticity of polycrystalline γ-TiAl-based intermetallic alloys. Issue 24 (7th June 2018) - Liu, Shiqiu; Ding, Hongsheng; Zhang, Hailong; Chen, Ruirun; Guo, Jingjie; Fu, Hengzhi
Abstract : High-density deformation γ nanotwins could realize large improvement of room-temperature plasticity and strength in polycrystalline γ-TiAl based intermetallic alloys. Abstract : Intermetallic alloys with high melting point can mostly serve as promising high-temperature structural materials, but their intrinsic brittleness limits their further application. Herein, we developed a strategy to realize high strength and high plasticity simultaneously in Cr-rich γ-TiAl-based intermetallic alloys via introducing high-density deformation nanotwins. Non-equilibrium continuous casting followed by annealing in the (α + γ) phase region generated numerous Shockley partial dislocations and stacking faults as well as a number of α2 nanoparticles in the γ-TiAl phase. The substantial Shockley partial dislocations and stacking faults acting as effective heterogeneous nucleation sites favored the generation of high-density nanotwins in the as-annealed alloys during deformation, especially within the γ lamellae. This strategy can also be applied to other brittle alloys with a favorable twinning deformation mechanism and paves the way for the development of high-strength and high-ductility materials.